Concurrent intestinal malrotation and Meckel’s diverticulum presenting as acute intestinal obstruction in an adult - Manohar, Aishwarya Emerald; Kumar, M. S. Kalyan; Vijayalakshmi, V.; Kannan, R. (International Surgery Journal, 2021)
Intestinal malrotation is the partial or complete failure of rotation of midgut around the superior mesenteric artery, while Meckel’s diverticulum is the remnant of vitellointestinal duct and concurrence of these congenital abnormalities in an adult is considered a rarity. Till date only 3 cases of concurrent intestinal malrotation and Meckel’s diverticulum have been reported. We report a 18 years male who presented with a 3 day history of abdominal pain, bilious vomiting, obstipation and chronic abdominal pain on and off since 3 years of age. During the last episode which occurred 1 year back, he was diagnosed with intestinal malrotation with subacute intestinal obstruction and was treated conservatively. Examination revealed the presence of signs of peritonitis. After resuscitation, CECT abdomen was taken which showed dilated small bowel loops in the subhepatic region associated with malrotation. Emergency laparotomy revealed a Ladd’s band below which the gangrenous small bowel loops 150 cm from the duodenojejunal (flexure until 5 cm proximal to the ileocecal junction) were found herniating into the subhepatic region with a Meckel’s diverticulum and a right sided DJ flexure. We proceeded with the band release and resection of gangrenous bowel followed by proximal jejunostomy with distal ileostomy. HPE was consistent with Meckel’s diverticulitis without any ectopic gastric or pancreatic mucosa. Ostomy reversal was done after 8 weeks. Patient had an uneventful postoperative recovery during both the admissions and he is on regular follow-up now.